The history of MF59® adjuvant: a phoenix that arose from the ashes. (January 2013) - O'Hagan, Derek T; Ott, Gary S; Nest, Gary Van; Rappuoli, Rino; Giudice, Giuseppe Del
The first clinical trial of an MF59 ® -adjuvanted influenza vaccine (Novartis) was conducted 20 years ago in 1992. The product that emerged (Fluad ®, Novartis) was licensed first in Italy in 1997 and is now licensed worldwide in 30 countries. US licensure is expected in the coming years. By contrast, many alternative adjuvanted vaccines have failed to progress. The key decisions that allowed MF59 to succeed in such a challenging environment are highlighted here and the lessons that were learned along the way are discussed. MF59 was connected to vaccines that did not succeed and was perceived as a 'failure' before it was a success. Importantly, it never failed for safety reasons and was always well tolerated. Even when safety issues have emerged for alternative adjuvants, careful analysis of the substantial safety database for MF59 have shown that there are no significant concerns with widespread use, even in more 'sensitive' populations.